Three-dimensional electron backscattered diffraction analysis of deformation in MgO micropillars - Korte, Sandra; Ritter, M.; Jiao, C.; Midgley, P. A.; Clegg, W. J. (Acta Materialia, 2011)
Small-scale testing is extensively used to study the effects of size on plasticity or characterise plastic deformation of brittle materials, where cracking is suppressed on the microscale. Geometrical and experimental constraints have been shown to affect small-scale deformation and efforts are underway to understand these better. However, current analytical techniques tend to possess high resolution in only one or two dimensions, impeding a detailed analysis of the entire deformed volume. Here electron backscattered diffraction in three dimensions is presented as a way of characterising three-dimensional (3-D) deformation at high spatial resolution. It is shown that, by reconstruction of compressed and then successively sliced and indexed MgO micropillars, this 3-D technique yields information complementary to μ-Laue diffraction or electron microscopy, allowing a correlation of experimental artefacts and the distribution of plasticity. In addition, deformation features which are difficult to visualise by standard scanning electron microscopy are easily detected, for example where only small surface traces are produced or minimal plastic strain can be introduced before failure in brittle materials. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Compression test; Crystalline oxides; Electron backscattering diffraction; Plastic deformation; Scanning electron microscopy